La protesi monocompartimentale - Fantasia, F.; Placella, G. (Lo Scalpello - Journal, 2019)
UNICOMPARTMENTAL KNEE ARTHROPLASTY The concept of unicondylar knee arthroplasty (UKA) has been described as early as the 1950’s following the introduction of the MacIntosh and McKeever hemiarthroplasty. With improvements in implant design, patient selection, and surgical technique, there has been an increase in the use of UKA as a less-invasive alternative that offers faster recovery compared to total joint arthroplasty in the treatment of localized symptomatic osteoarthritis. The key points are: the precise indication, which has been perfected over time and with experience, and the improvement of the surgical technique used. These have led to less complications and an increase in the number of implanted UKAs, for both the medialis and the lateral side. The purpose of this article is to analyze what were the changes over time regarding the indications and what are currently the success rates for medial e lateral UKA.